SiO₂ nanomaterial as a tool to improve Hordeum vulgare L. tolerance to nano-NiO stress - Soares, Cristiano (2018)
This work was designed to assess the potential role of silicon dioxide nanomaterial (nano-SiO 2) in enhancing barley's tolerance to nickel oxide nanomaterial (nano-NiO). For this purpose, plants were grown for 14 days under nano-NiO (120 mg kg − 1 ) single and co-exposure with nano-SiO 2 (3 mg kg − 1 ). The exposure of barley to nano-NiO caused a significant decrease in growth-related parameters and induced a negative response on the photosynthetic apparatus. However, upon nano-SiO 2 co-exposure, the inhibitory effects of nano-NiO were partially reduced, with lower reductions in fresh and dry biomass, and with the recovery of the photosynthesis-related parameters. Plants growing under nano-NiO stress showed an overproduction of superoxide anion (O 2 − ), which favored the occurrence of oxidative stress and the enhancement of lipid peroxidation (LP), but the co-treatment with nano-SiO 2 reverted this tendency, generally lowering or maintaining the levels of LP and stimulating the redox pathway of thiols. The evaluation of the antioxidant (AOX) system revealed that nano-NiO induced the accumulation of proline, along with a decrease in ascorbate in leaves. Furthermore, superoxide dismutase (SOD) activity was significantly enhanced and catalase (CAT) and ascorbate peroxidase (APX) seemed to have a pivotal role in H 2 O 2 detoxification in leaves and roots, respectively. The response of the AOX system was even more prominent upon nano-SiO 2 co-exposure, reinforcing the ameliorating functions of this nanomaterial. Overall, the present study highlighted the protective role of nano-SiO 2 in barley plants under nano-NiO stress, possibly due to the Si-mediated protection against oxidative stress, by a more proactive performance of the plant AOX system.